Imiquimod treatment for Equus caballus papillomavirus infection in equine aural plaques - Zakia, Luiza S. [UNESP]; Olivo, Giovane [UNESP]; Basso, Roberta M. [UNESP]; Mira, Juliana [UNESP]; Herman, Mariana [UNESP]; Araujo, Joao P. [UNESP]; Borges, Alexandre S. [UNESP]; Oliveira-Filho, Josï¿½ P. [UNESP] (Wiley, 2016)
Background: Aural plaques are a dermatopathy associated with Equus caballus papillomavirus (EcPV). This disease affects horses of all ages, genders and breeds, and causes sensitivity of the ears. Hypothesis/Objectives: The aim of this study was to evaluate the clinical efficacy of 5% imiquimod cream for the treatment of aural plaques and to compare the PCR detection of EcPV 3, 4, 5 and 6 before and after treatment. Animals: Eight horses diagnosed with aural plaques (14 ears) were used. Three mares with unilateral aural plaques were used as untreated controls. Methods: Imiquimod cream was applied every 48 h until complete resolution of the aural plaques was observed. Animals were evaluated clinically for 180 days after the end of treatment. PCR for detecting EcPV 3, 4, 5 and 6 was performed using aural plaque biopsies collected before and at 90 days after the end of treatment. Results: Clinical resolution was observed in 93% of the treated ears. Imiquimod treatment promoted the clearance of EcPV in 71.4% of the treated ears. Clinical remission of the aural plaques and changes in EcPV DNA positivity between the first and second biopsies were not observed in the control group. In 75% of horses, sedation was required in order to carry out pretreatment cleaning. Conclusions: The results of this study support the hypothesis that 5% imiquimod cream may be used as an effective treatment for aural plaques in horses.